2020
DOI: 10.1038/s41598-020-64062-9
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and predictive factors by Bax, Caspases 3/9, Bcl-2, p53 and Ki-67 in prostate cancer after 12 Gy single-dose

Abstract: Radio-induced apoptosis is mediated by the activation of tumor protein p53, Bax and caspases. The purpose of this study was to investigate the early activation of this pathway in men receiving in vivo irradiation immediately before radical prostatectomy for locally advanced prostate cancer. We also investigated cell proliferation index (Ki-67), proto-oncogene (p53) and anti-apoptotic protein (Bcl-2) levels as potential predictive factors. We selected a homogeneous sample of 20 patients with locally advanced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…This can be observed on the increased expression of BAX and Apaf-1 in embryos with glucose 3% exposure. Earlier research studies showed that BAX has an important role in apoptosis process due to ROS, and increased BAX expression correlates with increased apoptosis rate [28][29][30][31]. The result of this study is linear to earlier studies which stated that increased Apaf-1 expression can increase apoptosis rate in zebrafish embryo through mitochondria-dependent pathway [32][33][34].…”
Section: Salacca Zalacca Peel Reduces Il-1β and Apoptosis Markers Expression Due To High Glucosesupporting
confidence: 86%
“…This can be observed on the increased expression of BAX and Apaf-1 in embryos with glucose 3% exposure. Earlier research studies showed that BAX has an important role in apoptosis process due to ROS, and increased BAX expression correlates with increased apoptosis rate [28][29][30][31]. The result of this study is linear to earlier studies which stated that increased Apaf-1 expression can increase apoptosis rate in zebrafish embryo through mitochondria-dependent pathway [32][33][34].…”
Section: Salacca Zalacca Peel Reduces Il-1β and Apoptosis Markers Expression Due To High Glucosesupporting
confidence: 86%
“…Caspases are known key players in apoptosis (Sadowski-Debbing et al 2002;Pisani et al 2020). On assessment of caspases 9 and 3 levels, the significant increase in levels of the enzymes recorded at 300 and 400 mg/kg suggests that metformin actually induces cell death via mitochondria-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was the result of multi-molecule co-regulation, among which the Bcl-2 family and the Caspase family are two important parts of regulating apoptosis. The Bcl-2 protein family includes both Bax pro-apoptotic members and Bcl-2 anti-apoptotic members, which were closely related to the Caspase family [44]. Bcl-2 can regulate cell apoptosis through Caspase-9 and Caspase-3 dependent pathways, which means that by increasing Bax and reducing Bcl-2 expression, it can stimulate mitochondria to release cytochrome C, and cytochrome C further recruits Caspase-9 to promote the formation of apoptotic bodies,and then induces the activation of Caspase-3 and triggers the Caspase cascade, which ultimately leads to apoptotic cell death [45,46].…”
Section: Discussionmentioning
confidence: 99%